The Influence of Employee Work Motivation on Service Performance of the Health Service Office in Hulu Sungai Utara Regency - Muhammad Reza Karimi (PT Mattawang Mediatama Solution, 2022)
This study aims to determine how much work motivation influenced service performance at the HSU District Health Office. In this study, the writer used a quantitative approach using associative research methods to determine the relationship between two or more variables. Meanwhile, the research instrument used a Likert scale to measure respondents' responses. Furthermore, this study's population was all HSU District Health Office employees, totalling 71 respondents. At the same time, the sample in this study was a saturated sampling technique, or all respondents of the population may be a sample. The study showed that work motivation value (x) results at the Hulu Sungai Utara District Health Office achieved 70.08%. Meanwhile, the service performance value (y) at the Hulu Sungai Utara District Health Office achieved 70.99%. On the other hand, there was a positive and significant influence between employee work motivation and service performance at the HSU District Health Office. Furthermore, Employee Work Motivation had an effect of 51.9% on employee performance. It can be seen from the model summary table, which states that the R square was 0.519. Similarly, there was an effect of Employee Work Motivation on the service performance of the HSU District Health Office. It can be seen with a significance of = 0.05 with t-test results of = 8,636 and α significance of < 0.05 (0.000 <0.05). In addition, the role of the head of a service was to be influential in improving performance in the office. Thus, the head of service can set a good example, motivate subordinates, and pay special attention to employees who excel to be given rewards or bonuses outside the basic salary. Thus, it can increase the employee's enthusiasm to improve performance and serve the community